Determining optimal locations for urgent care centres in Cornwall using computer modelling. Issue 7 (2nd July 2019) - Chalk, Daniel
Abstract : Background/Aims: Urgent care centres provide a broad range of services in comparison to minor injury units. In order to establish new urgent care centres, the Sustainability and Transformation Partnership in Cornwall aimed to identify the optimal number and location for these centres, which could then help to reduce the volume of patients attending emergency departments. Methods: A computer model that calculated average and maximum travel times, along with number of attendances, for over 4000 potential urgent care centre geographic configurations, was developed. The model predicted that establishing five urgent care centres would significantly minimise travel times for patients across the county. The model also predicted the locations for these centres that would minimise average travel times. Results: The results from the model were used to directly inform a decision made by the Sustainability and Transformation Partnership. Conclusion: The first urgent care centres in Cornwall, at Treliske, Bodmin Community Hospital and West Cornwall Hospital, were established in 2018. The urgent care centre in West Cornwall is now accepting patients; the two other sites are still under construction.